Efektivitas enzim kasar kitinase dari jamur Trichoderma viride yang diiradiasi oleh sinar gamma terhadap degradasi cangkang telur nematoda Haemonchus contortus pada ternak domba - Devi Indrawati; Ari Susilowati; Dadang Priyo Atmojo; Nana Mulyana (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2019)
The aim of this study was to determine increasing of chitinase crude enzyme activity produced by Trichoderma viride at different gamma irradiation doses and to know the degradation on the eggshell of Haemonchus contortus. Eggs of Haemonchus contortus were isolated from sheep feces using buoyant centrifugation method. The qualitative test of chitinase was conducted by inoculating Trichoderma viride irridiated by  variation gamma doses control, 250 Gray, 500 Gray, 750 Gray and 1000 Gray on the media of colloidal chitin agar. The quantitative test was conducted by measuring chitinase activity using colorimetric method based on specific enzyme activity and determination of dissolved protein levels. Shell changes were observed microscopically while N-acetyl glucosamine levels and dissolved protein levels were measured using spectrophotometer. Data were analyzed using One Way Analysis of Variance (ANOVA) with significance of the 95% and continued with Duncan’s Multiple Range Test  (DMRT test). The results showed that gamma irradiation doses treatment increase of chitinase crude enzyme activity produced by Trichoderma viride. At a dose of 500 Gray, Trichoderma viride had the optimum chitinase specific activity i.e. 0.30 U/mg. Furthermore, chitinase crude enzyme effective to degrade all layers of the eggshell of Haemonchus contortusand the higher the concentration of crude enzyme given, the greater the level of egg damaged.